GREEN ECONOMY : AGRICULTURAL SECTOR VALUATION TO CREATE FOOD SECURITY IN JAKARTA CITY IN SHARIA PERSPECTIVE - Edi Wahyu Wibowo; Darwati Susilastuti; Meirinaldi (FORPIM PTKIS ZONA TAPAL KUDA, 2022)
ABSTRACTThe agricultural sector is one of the most important sectors for a region, because this sector will support the provision of food, so that the region creates food security. Preservation of the environment with a perspective based on Maqashid al-Shari'ah in order to achieve benefit in the world and the hereafter. This study will analyze the green economy valuation of the agricultural sector so that it can determine the food needs in Jakarta, and provide solutions so that Jakarta can become a city that has food security for its citizens. The results of this study showed that the value of the degradation of food needs in Jakarta in 2019 was Rp. 15,902,260 and in 2020 it was Rp. 16,182,279. So that the value of green GDP in 2019 will be minus 14,504,043 and in 2020 it will be minus 14,781,212. The urban farming program is one of the best solutions in overcoming this food security problem, by utilizing vacant land around the house yard. With urban farming, the people of Jakarta are assisted in basic needs.Keywords: Green GDP, Degradation, Food Security